ANALISIS STUDI KELAYAKAN USAHA CHRISTINE KLAPPERTAART DI KAIRAGI WERU MANADO - Yestelin . Kawoka; Ventje V. Rantung; Caroline B.D. Pakasi (AGRI-SOSIOEKONOMI, 2015)
This study aims to determine the feasibility of Christine klapertaart in terms of non financial aspect and financial aspects.The result showed that non financial feasibility analysis shows Christine klapertaart feasible to proceed with supported aspects. Financial feasibilty analysis with 100 own capital is feasible with NPV value at df 18%., IRR is more than prescribed interest rate 18%, the value Profitability Index more than 1. Payback period shows that this business have returned investment within 2 years and 6 months 27 days.